Cytotoxicity, Antiadipogenic, Low-Density Lipoprotein Oxidation Inhibitory Activities, and Acute Toxicity Study of Psychotria densinervia Hydroethanolic Leaf and Bark Extracts - Jean Romuald Mba; Djamila Zouheira; Stephanie Tamdem Guetchueng; Hadidjatou Daïrou; Paul Toukam Djouonzo; Lawrence Ayong; Jules-Roger Kuiate; Gabriel A. Agbor (The Scientific World Journal)
Conclusion: Based on the results obtained, the P. densinervia hydroethanolic leaf extract possesses a better antioxidant and antiadipogenic activities than the bark extract.